Efektivitas Aromaterapi Jeruk Nipis Terhadap Dismenore Pada Remaja Putri - Sambo, Mery; Madu, Yunita Gabriela; Sampe, Anita; Reski, Eva; Rombon, Friskalia Marcela M. (Jurnal Keperawatan Florence Nightingale, 2024)
Dysmenorrhea is a painful condition during menstruation which can have an impact on teenagers' activities or activities, especially at school, thereby disrupting learning activities and affecting school performance. Treatment with drugs can cause undesirable side effects, for this reason it is necessary to provide non-pharmacological therapy to avoid the side effects of long-term use of pharmacology. One non-pharmacological action that can be given is aromatherapy. The aim of this research is to determine the effectiveness of lime aromatherapy on dysmenorrhea in teenagers at Frater Kumala Makassar High School. Design of research used was pre-experimental with a one group pre-test and pos- test design approach. Sampling used a probability sampling method with a simple random sampling approach with a sample size of 27 respondents. The instrument used was the Numeric Rating Scale (NRS) checklist sheet to determine the level of dysmenorrhea pain before and after being given lime aromatherapy. Data analysis used the Wilcoxon statistical test with a significance value of a = 0.05. The result was p = 0.000, so it was concluded that peppermint aromatherapy and lime aromatherapy were effective against dysmenorrhea in adolescents